Serotonergic modulation of post-synaptic inhibition and locomotor alternating pattern in the spinal cord - Gackière, Florian; Vinay, Laurent (Frontiers in Neural Circuits, 2014)
The central pattern generators (CPGs) for locomotion, located in the lumbar spinal cord, are functional at birth in the rat. Their maturation occurs during the last few days preceding birth, a period during which the first projections from the brainstem start to reach the lumbar enlargement of the spinal cord. Locomotor burst activity in the mature intact spinal cord alternates between flexor and extensor motoneurons through reciprocal inhibition and between left and right sides through commisural inhibitory interneurons. By contrast, all motor bursts are in phase in the fetus. The alternating pattern disappears after neonatal spinal cord transection which suppresses supraspinal influences upon the locomotor networks. This article will review the role of serotonin (5-HT), in particular 5-HT2 receptors, in shaping the alternating pattern. For instance, pharmacological activation of these receptors restores the left-right alternation after injury. Experiments aimed at either reducing the endogenous level of serotonin in the spinal cord or blocking the activation of 5-HT2 receptors. We then describe recent evidence that the action of 5-HT2 receptors is mediated, at least in part, through a modulation of chloride homeostasis. The postsynaptic action of GABA and glycine depends on the intracellular concentration of chloride ions which is regulated by a protein in the plasma membrane, the K+-Cl− cotransporter (KCC2) extruding both K+ and Cl− ions. Absence or reduction of KCC2 expression leads to a depolarizing action of GABA and glycine and a marked reduction in the strength of postsynaptic inhibition. This latter situation is observed early during development and in several pathological conditions, such as after spinal cord injury, thereby causing spasticity and chronic pain. It was recently shown that specific activation of 5-HT2A receptors is able to up-regulate KCC2, restore endogenous inhibition and reduce spasticity.